Viral hepatitis A infection amidst Covid-19 outbreak in central part of Sri Lanka - K. D. S. T. Abeywardana; M. A. R. V. Muthugala (Sri Lankan Journal of Infectious Diseases, 2022)
The COVID-19 pandemic has caused resource depletion and a shift in priorities in the public health system, impacting the control of other communicable diseases of  public interest. Hepatitis A virus is a notifiable disease transmitted through faeco-oral transmission. We conducted a retrospective analysis of patients with a clinical diagnosis of hepatitis whose specimens were submitted to the Virology Laboratory of the National Hospital, Kandy, from January 2019 to December 2021. During pre-pandemic time 28 (4.4%) were positive for hepatitis A, while it was 86 (10.2%) during the pandemic. There was a statistically significant difference in incidence between the two cohorts (p < 0.0001). The majority of patients in 2021 (25 patients; 64.1%) resided in Badulla. Our data shows an increased incidence of hepatitis A cases during the pandemic, and residents in Badulla were predominantly affected in 2021. Strategies should therefore be undertaken to prevent further cases in the central part of the country.